Highlighting the Magnitude of Work Motivation and Teamwork in Developing and Exploiting Human Capital: An Autoethnographic Study - Doshi, Rahul (2010)
This research aims to emphasize the need and importance of work motivation and teamwork in the management and development of human capital. Employees form the backbone of companies and motivating them rightly can ensure success for any organization. In this research, I look to explore these boundaries by reflecting on some past incidents specifically on motivation and teamwork. By using autoethnography as a source of data collection, I am better able to relate and identify the need for personalized motivation. The findings prove to contradict as well as complement the literature review, inevitably contributing to the need for managers to understand the significance of motivating their staff.